Literature Review: Pengaruh Efikasi Diri dan Konformitas Teman Sebaya terhadap Perilaku Menyontek Siswa - Fitriah, Siti Shalma (Journal of Psychology and Treatment, 2022)
Bad behavior or what we often call deviant behavior still often occurs in the environment where we live, one of the behaviors that is still carried out by students at school today. This is motivated by the pressure felt by students to get high grades, making them do various ways to achieve it, including doing fraudulent things in the world of education. One of the mistakes that often occurs in the world of education is cheating behavior which makes students dishonest in doing assignments and exams. Cheating behavior is often associated with self-efficacy or self-efficacy. and also peer conformity. The method used in this research is literature study obtained from reference books and relevant journal articles to identify the concept of alignment with the theme of this research.